113k views
3 votes
How do you solve -3 + 5 +6g =11 - 3g?

User Zinglon
by
5.4k points

2 Answers

2 votes

Final Answer:
g = 1

Steps/Reasons/Explanation:

Question: How do you solve
-3 + 5 +6g = 11 - 3g?

Step 1: Simplify
-3 + 5 + 6g to
6g + 2.


6g + 2 = 11 - 3g

Step 2: Subtract
2 from both sides.


6g = 11 - 3g - 2

Step 3: Simplify
11 - 3g - 2 to
-3g + 9.


6g = -3g + 9

Step 4: Add
3g to both sides.


6g + 3g = 9

Step 5: Simplify
6g + 3g to
9g.


9g = 9

Step 6: Divide both sides by
9.


g = 1

~I hope I helped you :)~

User Jeremy Dunn
by
4.9k points
0 votes
Add -3 +5 u get 2
the add 3g to 6g to get 9g
then u have 2+9g=11
subtract 2 to both sides u get 9g=9
divide 9 u get 1=g hope I helped
User Rodling
by
4.4k points